EDUKASI PENCEGAHAN STUNTING PADA BALITA MELALUI PEMBERDAYAAN KELUARGA DI KELURAHAN BELAWAN BAHAGIA - Ngatno Sahputra; Lukman Hakim Siregar; Tommi Jafisa (Unity Academy, 2023)
Nutritional Problems (Stunting) is a lack of nutritional intake for a long time during the first 1000 days of life (HPK), which is a critical period, causing the child's growth to be disrupted, namely the child's height is lower or shorter (stunted) than his age. Stunting in Medan City is increasingly worrying, from 21 sub-districts in Medan City, 20 of them have found cases of stunting. Belawan District was the largest contributor with 142 children affected by stunting. Belawan Bahagia Village, as stated directly by the Head of the Village, Mr. Faihsyal Amil, S.Sos, who stated that since February 2022 in Belawan Bahagia Village, the number of Stunting babies was 5 people until August 2022, the number had increased to 15 people. The aim of the activity is to increase nutritional knowledge and behavior in an effort to prevent stunting. Educational activities on the theme of stunting were carried out among families in the Belawan Selamat sub-district, 5 representatives from the sub-district, 21 respondents from heads of families suffering from stunting. This activity is carried out through direct outreach. Through this activity the service team delivers material in a previously designed seminar manner. The material presented was entitled